Perda de Receitas da Inflação e Defesa da Lucratividade dos Grandes Bancos, no Início do Plano Real - Carlos Eduardo Carvalho (Revista de Economia Mackenzie, 2005)
The largest Brazilian banks adapted quickly to the sharp reduction in inflationary gains resulting from the Plano Real of 1994. This performance is largely explained by the strengthening of most large banks in previous years, supported by the institutional practices and rules and by the economic policies developed to adapt Brazilian economy to the high inflation and serious exchange crisis. The study analyzes the relations between banks and inflation in Brazil in the 1980s and early 1990s and in the transition to low inflation.